![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Gọi tổng trên là A
Ta có : \(A=\frac{1}{5}+\frac{1}{10}+\frac{1}{20}+...+\frac{1}{2560}\)
\(2A=2\left(\frac{1}{5}+\frac{1}{10}+...+\frac{1}{2560}\right)\)
\(2A=\frac{2}{5}+\frac{1}{5}+\frac{1}{10}+...+\frac{1}{1280}\)
\(2A-A=\left(\frac{2}{5}+\frac{1}{5}+...+\frac{1}{1280}\right)-\left(\frac{1}{5}+\frac{1}{10}+...+\frac{1}{2560}\right)\)
\(A\left(2-1\right)=\frac{2}{5}-\frac{1}{2560}\)
\(A.1=\frac{1024}{2560}-\frac{1}{2560}\)
\(A=\frac{1023}{2560}\)
Ta có : A = 1/5 + 1/10 + 1/20 + ... + 1/2560
2A = 2 ( 1/5 + 1/10 + ... + 1/2560 )
2A = 2/5 + 1/5 + 1/10 + .. + 1/2560
2A - A = ( 2/5 + 1/5 + ... + 1/1280 ) - ( 1/5 + 1/10 + ... + 1/2560 )
A = 2 - 1 = 2/5 - 1/2560
A.1 = 1024/2560 - 1/2560
A = 1023 = 2560
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{7}{4}-y\)x \(\frac{5}{6}=\frac{1}{2}+\frac{1}{3}\)
\(\frac{7}{4}-y\)x \(\frac{5}{6}=\frac{5}{6}\)
\(y\) x \(\frac{5}{6}=\frac{7}{4}-\frac{5}{6}\)
\(y\) x \(\frac{5}{6}=\frac{11}{12}\)
y == \(\frac{11}{12}:\frac{5}{6}\)
y == \(\frac{11}{10}\)
Ta có \(\frac{7}{4}-\frac{5}{6}y=\frac{5}{6}\)
\(\frac{7}{4}=\frac{5}{6}y+\frac{5}{6}\)
\(\frac{7}{4}=\frac{5}{6}\left(y+1\right)\)
\(\frac{7}{4}:\frac{5}{6}=y+1\)
\(\frac{7}{4}\cdot\frac{6}{5}=\frac{21}{10}=y+1\)
\(y=\frac{21}{10}-1=\frac{11}{10}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2\frac{3}{4}+1\frac{5}{6}+3\frac{1}{4}+2\frac{1}{6}\)
= \(\frac{11}{4}+\frac{11}{6}+\frac{13}{4}+\frac{13}{6}\)
= \(\left(\frac{11}{4}+\frac{13}{4}\right)+\left(\frac{11}{6}+\frac{13}{6}\right)\)
= \(\frac{24}{4}+\frac{24}{6}\)
= \(6+4\)
= \(10\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{2}{3}.\frac{4}{5}+\frac{1}{3}.\frac{4}{5}=\frac{4}{5}\left(\frac{2}{3}+\frac{1}{3}\right)=\frac{4}{5}.\frac{3}{3}=\frac{4}{5}.1=\frac{4}{5}\)
\(\frac{1}{2}:\frac{3}{4}+\frac{1}{6}:\frac{3}{4}=\frac{3}{4}:\left(\frac{1}{2}+\frac{1}{6}\right)=\frac{3}{4}:\frac{2}{3}=\frac{9}{8}\)
\(\frac{2}{3}.\frac{4}{5}-\frac{1}{3}.\frac{4}{5}=\frac{4}{5}\left(\frac{2}{3}-\frac{1}{3}\right)=\frac{4}{5}.\frac{1}{3}=\frac{4}{15}\)
\(\frac{1}{2}:\frac{3}{4}-\frac{1}{6}:\frac{3}{4}=\frac{3}{4}:\left(\frac{1}{2}-\frac{1}{6}\right)=\frac{3}{4}:\frac{1}{3}=\frac{9}{4}\)
\(\frac{2}{3}.\frac{4}{5}+\frac{1}{3}.\frac{4}{5}=\left(\frac{2}{3}+\frac{1}{3}\right).\frac{4}{5}=1.\frac{4}{5}=\frac{4}{5}\)
\(\frac{1}{2}:\frac{3}{4}+\frac{1}{6}:\frac{3}{4}=\frac{1}{2}.\frac{4}{3}+\frac{1}{6}.\frac{4}{3}=\left(\frac{1}{2}+\frac{1}{6}\right).\frac{4}{3}=\frac{2}{3}.\frac{4}{3}=\frac{8}{9}\)
c,d tương tự
\(2\frac{1}{3}:3\frac{1}{4}\)
\(=\frac{7}{3}:\frac{13}{4}\)
\(=\frac{28}{39}\)
=7/3:13/4
=7/3*4/13=28/39